PENGARUH HASIL ANALISIS FUNDAMENTAL TERHADAP RETURN SAHAM PT RAMAYANA LESTARI SENTOSA TBK - Herdiyana Herdiyana; Kartika Kartika (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2015)
The company can be knowledge have a good fundamentals if the company has current assets that are notbloated and mediocre sales, total assets and total capital is greater than the total debt, and the value ofEarning Per Share has a positive growth over the last five years. The higher the earning per share, thehigher the stock price. This contrasts with the fact that of the PT Ramayana Lestari Sentosa, Tbk becausethe company has current assets increased growth while the sales growth rate decreased in the period2008-2009. The method used in this research is explanatory survey. The study states that the resultsobtained in the Current Ratio and Debt to Equity Ratio, due to the variable multikolinearitas problemoccurs during testing. Total Asset Turnover and Net Profit Margin partially influence on stock prices.Total Asset Turnover partial effect on stock returns, while Net Profit Margin partially no effect on stockreturns. Simultaneously Total Asset Turnover and Net Profit Margin is the result of fundamental analysisinfluence on stock prices and stock returns.